Modeling of the deposition of Na Clusters on MgO(001) - Bär, M.; Dinh, P. M.; Moskaleva, L. V.; Reinhard, Paul-Gerhard; Rösch, N.; Suraud, E. (Physical Review B - Condensed Matter and Materials Physics, 2009)
We investigate the dynamics of deposition of small Na clusters on MgO(001) surface. A hierarchical modeling is used combining quantum mechanical with molecular mechanical description. Full time-dependent density-functional theory is used for the cluster electrons while the substrate atoms are treated at a classical level. We consider Na6 and Na8 at various impact energies. We analyze the dependence on cluster geometry, trends with impact energy, and energy balance. We compare the results with deposit on the much softer Ar(001) surface. © 2009 The American Physical Society.
CRIS-Team Scopus Importer:2023-07-24